Comparação do efeito imediato de exercício do método Lee Silverman Voice Treatment® versus trato vocal semiocluído em pacientes com doença de Parkinson - Pinheiro, Renata Serrano de Andrade (2015)
INTRODUCTION - Parkinson's disease (PD) was first described in the early nineteenth century by James Parkinson. It is characterized by the presence of involuntary trembling movements, decreased muscle strength, tendency to body lean forward and gait. In Parkinson's disease occur several changes that affect the voice and speech. OBJECTIVE - The aim of this study was to compare the immediate effect of exercises Lee Silverman Voice Treatment® method (LSVT) versus Semi-occluded vocal tract in the vocal behavior of patients with Parkinson's disease. METHOD - The chapters have been described in the form of scientific articles, the first is a systematic review of the literature article entitled "Scientific evidence and restrictions of voice treatment in Parkinson's disease: a systematic review", the second is entitled "Evaluation of quality of life and vocal symptoms in view of the patient with Parkinson's disease ", and the third with the title" Comparison of the immediate effect of the Lee Silverman Voice exercises Treatment® versus Vocal Tract Semi-occluded in patients with Parkinson's disease. " RESULTS - The first article highlights the articles found in the forms of treatment: medication, surgical and rehabilitation for Parkinson's disease, referring to the sample of studies, the methods and techniques used and the completion of each study. The main methods and techniques used for vocal rehabilitation found in the article were: LSVT, Ear Monitoring, Wind Instrument and Music Therapy. In the second article the individuals affected by PD reported change in their quality of life and voice and vocal symptoms, which impact on their daily lives, which are arising from the vocal disorder triggered by the disease which have been achieved. And the third article showed that the immediate effects of exercise of the Lee Silverman Voice Vocal Tract Treatment® versus Semi-occluded cause the vast majority of benefits similar to the vocal parameters of acoustic analysis and perceptual evaluation of individuals with PD. CONCLUSION - The scientific production in the voice area that deals with Parkinson's disease is still scarce, the expansion of research that show new options of treatment methods and techniques for the voice that is increasingly necessary. The use of instruments of vocal self-assessment, the population of Parkinson will assist in the evaluation and therapy with the intent to facilitate individual patients' perception of the different aspects of their vocal production. The immediate effect of the vocal tract exercises Semi-occluded with high-strength tube is an effective alternative in voice therapy of Parkinson's disease.